2021
DOI: 10.1093/brain/awab141
|View full text |Cite
|
Sign up to set email alerts
|

Kcnq2/Kv7.2 controls the threshold and bi-hemispheric symmetry of cortical spreading depolarization

Abstract: Spreading depolarization (SD) is a slowly propagating wave of massive cellular depolarization associated with acute brain injury and migraine aura. Genetic studies link depolarizing molecular defects in Ca2+ flux, Na+ current in interneurons, and glial Na+-K+ ATPase with SD susceptibility, emphasizing the important roles of synaptic activity and extracellular ionic homeostasis in determining SD threshold. In contrast, although gene mutations in voltage-gated potassium ion channels that shape intrinsic membrane… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 79 publications
(74 reference statements)
6
27
1
Order By: Relevance
“…In addition to proving that Kcnq2 is required for M‐channel activity from the embryonic stages, this study showed an increased transcription of the Kcnq3 and Kcnq5 genes, suggesting a compensatory mechanism following the loss of Kcnq2 expression 22 . Recently, several models with Kcnq2 deletion restricted to cortical pyramidal neurons and CA1 excitatory and inhibitory neurons were produced 23‐26 . They showed that Kcnq2 is required to regulate neuronal excitability through cortical spreading depolarization regulation, the increase of input resistance, action potential number, and medium afterhyperpolarization (mAHP) in pyramidal neurons 23‐25 .…”
Section: Knockout Modelsmentioning
confidence: 60%
“…In addition to proving that Kcnq2 is required for M‐channel activity from the embryonic stages, this study showed an increased transcription of the Kcnq3 and Kcnq5 genes, suggesting a compensatory mechanism following the loss of Kcnq2 expression 22 . Recently, several models with Kcnq2 deletion restricted to cortical pyramidal neurons and CA1 excitatory and inhibitory neurons were produced 23‐26 . They showed that Kcnq2 is required to regulate neuronal excitability through cortical spreading depolarization regulation, the increase of input resistance, action potential number, and medium afterhyperpolarization (mAHP) in pyramidal neurons 23‐25 .…”
Section: Knockout Modelsmentioning
confidence: 60%
“…Kv7.2 and Kv7.3 of Kv7 channels are predominantly expressed in trigeminovascular system (8–10). Additionally, in the study mentioned above (29) it was demonstrated that Kv7.2 channel activation inhibited the CSD. We therefore speculate that retigabine may exert its CGRP-reducing effects substantially through activation of Kv7.2 and/or Kv7.3.…”
Section: Discussionmentioning
confidence: 89%
“…3 B ). Importantly, knockin mice carrying the KCNQ2 3XFLAG epitope were viable, with no evidence of increased lethality or behavioral seizures, which occur in animals with reduced KCNQ2 channel activity ( 14 , 33 , 34 ). Additionally, births followed a Mendelian distribution when heterozygous Kcnq2 flag/+ mice were bred together (18 wild-type: 25.7%; 32 heterozygous: 45.7%; 20 homozygous: 28.6%), consistent with normal KCNQ2 function.…”
Section: Resultsmentioning
confidence: 99%